How Do Structurally Distinct Compounds Exert Functionally Identical Effects in Combating Obesity? - Deng, Zhi-Jun; Liu, Ruo-Xuan; Li, A-Rong; Guo, Jie-Wen; Zeng, Qing-Ping (Frontiers in Pharmacology, 2018)
Although the concept of inflammatory obesity remains to be widely accepted, a plethora of antibiotics, anti-inflammatory agents, mitochondrial uncouplers, and other structurally distinct compounds with unknown mechanisms have been demonstrated to exert functionally identical effects on weight reduction. Here we summarize a universal mechanism in which weight loss is modulated by mitochondrial biogenesis, which is correlated with conversion from the mitochondria-insufficient white adipose tissue to the mitochondria-abundant brown adipose tissue. This mechanistic description of inflammatory obesity may prove useful in the future for guiding pathology-based drug discovery for weight reduction.